Adaptive Islamic Education Curriculum Model in the Society 5.0 Era: A Literature Study from Technology and Humanism Perspectives - Abdul Rouf (QAWIUN : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
The rapid expansion of digital innovation in the Society 5.0 era requires an Islamic Education (PAI) curriculum that is more adaptive, flexible, and aligned with the learning needs of students living in a technology-driven environment. The curriculum is expected not only to respond to technological advancement but also to uphold Islamic humanistic values that center on character formation, spiritual development, and ethical consciousness. This study aims to conceptualize the characteristics of an adaptive PAI curriculum capable of harmonizing technological innovation with humanistic principles. A literature review method was employed by examining reputable journal articles, scholarly books, and scientific reports published in the last ten years using a thematic analytical approach. The findings reveal that adaptive curriculum design requires content flexibility, meaningful technology integration, reinforcement of humanistic values, and institutional readiness to implement innovative models. These results affirm that an adaptive Islamic Education curriculum is essential for preparing learners to navigate the complexities of the Society 5.0 era while remaining grounded in moderate, ethical, and value-oriented Islamic teachings